Regulatory Role of the Transcription Factor Twist1 in Cancer-Associated Muscle Cachexia - Razzaque, Mohammed S.; Atfi, Azeddine (Frontiers in Physiology, 2020)
Muscle cachexia is a common co-morbidity seen in the vast majority of advanced cancer patients, often associated with low quality of life and death due to general organ dysfunction. The triggering events and underlying molecular mechanisms of muscle wasting are not yet clearly defined. Our recent study has shown that the ectopic expression of Twist1 in muscle progenitor cells is sufficient to drive muscle structural protein breakdown and attendant muscle atrophy, reminiscent of muscle cachexia. Intriguingly, muscle Twist1 expression is highly induced in cachectic muscles from several mouse models of pancreatic ductal adenocarcinoma (PDAC), raising the interesting possibility that Twist1 may mediate PDAC-driven muscle cachexia. Along these lines, both genetic and pharmacological inactivation of Twist1 function was highly significant at protecting against cancer cachexia, which translated into a significant survival benefit in the experimental PDAC animals. From a translational perspective, elevated expression of Twist1 is also detected in cancer patients with severe muscle wasting, implicating a role of Twist1 in cancer cachexia, and further providing a possible target for therapeutic attenuation of cachexia to improve cancer patient survival. We have briefly summarize how Twist1 acts as a master regulator of tumor-induced cachexia, and discuss the relevance of our findings to muscle wasting diseases in general. The mechanism of decreased muscle mass in various catabolic conditions is thought to rely on similar pathways, and, therefore, Twist1-induced cachexia may benefit diverse groups of patients with clinical complications associated with loss of muscle mass and functions, beyond the expected benefits for cancer patients.